The Role of a Dolichol-Oligosaccharide as an Intermediate in Glycoprotein Biosynthesis - Hsu, An-Fei (1974)
Incubation of mouse myeloma microsomes with GDP-[(14)C]mannose results in the biosynthesis of [(14)C]mannose phosphoryl dolichol [Baynes, J. W., Hsu, A.-F. & Heath, E. C. (1973) J. Biol. Chem. 248, 5693-5704] and a [(14)C]mannose- and N-acetylglucosamine (GlcNAc)-containing oligosaccharide derivative of dolichol. Thus, [(14)C]mannose phosphoryl dolichol and [(14)C]mannose-labeled oligosaccharide pyrophosphoryl dolichol were isolated from incubation mixtures by solubilization in 2% (w/v) Triton X-100 and the lipids were separated from small molecules by gel filtration fractionation. After removal of radioactive protein from the preparation, the two lipid derivatives were separated quantitatively by fractionation on a concanavalin A-Sepharose column; [(14)C]mannose phosphoryl dolichol was not retained by the affinity resin but [(14)C]mannose-oligosaccharide pyrophosphoryl dolichol adsorbed to the gel and was eluted with α-methylmannoside.[(14)C]Mannose-oligosaccharide pyrophosphoryl dolichol appeared to be homogeneous when fractionated on DEAE-cellulose and in several thin-layer chromatographic systems. Treatment of [(14)C]mannose oligosaccharide pyrophosphoryl dolichol with 10% (w/v) NH(4)OH at 100° for 1 hr resulted in the formation of a water-soluble radioactive oligosaccharide phosphate which was isolated and characterized as [Man](5) → [GlcNAc → GlcNAc → P. Incubation of [(14)C]mannose-oligosaccharide pyrophosphoryl dolichol with myeloma microsomal preparations results in the transfer, presumably, of the entire oligosaccharide to endogenous protein. Kinetic studies indicate that the dolichol derivatives serve as intermediates in the glycosylation of protein as follows: [Formula: see text]